Analisis Pengawasan Pegawai Pada Kantor Badan Pusat Statistik (Bps) Kabupaten Nganjuk - Sutrisno, Sutrisno; Sulajtmiko, Sulajtmiko; Juniati, Lita (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
This research intends to objectively examine the implementation of direct supervision and indirect supervision of employee capacity building at the Nganjuk Regency Central Statistics Agency office. The research method used is qualitative descriptive, with the analysis section (respondents) being all employees of the Central Statistics Agency of Nganjuk Regency. The method of collecting information used is monitoring and question and answer. The results of the research show that the application for supervision, in this case direct and indirect supervision at the Central Bureau of Statistics of Nganjuk Regency, has not been carried out properly. This is due to the lack of understanding of employees about the obligations and responsibilities of each, lack of communication between orders and subordinates in the agency, employees who are less compliant and there is no motivation of employees in carrying out work. Ineffective supervision is caused by the lack of commitment to prevent and overcome irregularities. Direct observation has not been done very often, this can be seen from the number of employees who are not at the desk when the activity hours are running, many employees who arrive late are only tested during the morning assembly and come from an electric ambulance and are not tested the next day.